2012
DOI: 10.1175/waf-d-11-00070.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between GOES-12 Overshooting-Top Detections, WSR-88D Radar Reflectivity, and Severe Storm Reports

Abstract: Studies have found that convective storms with overshooting-top (OT) signatures in weather satellite imagery are often associated with hazardous weather, such as heavy rainfall, tornadoes, damaging winds, and large hail. An objective satellite-based OT detection product has been developed using 11-mm infrared window (IRW) channel brightness temperatures (BTs) for the upcoming R series of the Geostationary Operational Environmental Satellite (GOES-R) Advanced Baseline Imager. In this study, this method is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 24 publications
(22 reference statements)
1
51
0
1
Order By: Relevance
“…In addition to the climate impacts associated with overshooting convection, these storms have been shown to be associated with hazardous weather at the surface, such as flooding, hail, tornadoes, and damaging winds, and identification of overshooting tops as a predictor for severe weather has been explored (e.g., Negri 1982;McCann 1983;Brunner et al 2007;Setvák et al 2010;Bedka 2011;Dworak et al 2012). Furthermore, gravity wave generation, breaking, and induced turbulence near the tropopause from overshooting convection are major concerns for aircraft safety and flight planning (e.g., Lane et al 2003;Lane and Sharman 2006;Bedka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the climate impacts associated with overshooting convection, these storms have been shown to be associated with hazardous weather at the surface, such as flooding, hail, tornadoes, and damaging winds, and identification of overshooting tops as a predictor for severe weather has been explored (e.g., Negri 1982;McCann 1983;Brunner et al 2007;Setvák et al 2010;Bedka 2011;Dworak et al 2012). Furthermore, gravity wave generation, breaking, and induced turbulence near the tropopause from overshooting convection are major concerns for aircraft safety and flight planning (e.g., Lane et al 2003;Lane and Sharman 2006;Bedka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Adler et al (1983) found that most storms with this V-shape were related to severe weather (tornadoes, hail, and intense rain). The presence of overshooting clouds confirms strong updrafts within the storm often being associated with hazardous weather (Dworak et al, 2012). These types of clouds can be detected using spatial gradients of 11 µm BTs (Bedka et al, 2010;Bedka, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…Lett. 12 (2017) 074012 Dworak et al (2012) for an overview). The detection of OTs is therefore a relevant proxy for surface impacts of severe thunderstorms.…”
Section: Methodsmentioning
confidence: 99%